Diagnosis of Streptococcus pneumoniae infections in adults with bacteremia and community-acquired pneumonia: clinical comparison of pneumococcal PCR and urinary antigen detection. - Smith, MD; Sheppard, C; Hogan, A; Harrison, T; Dance, D; Derrington, P; George, R (2009)
The diagnosis of severe Streptococcus pneumoniae infection relies heavily on insensitive culture techniques. To improve the usefulness of PCR assays, we developed a dual-PCR protocol (targeted at pneumolysin and autolysin) for EDTA blood samples. This was compared to the Binax NOW S. pneumoniae urine antigen test in patients with bacteremic pneumococcal infections. Patients with nonbacteremic community-acquired pneumonia also were tested by these methods to determine what proportion could be confirmed as pneumococcal infections. A direct comparison was made in a group of patients who each had both tests performed. The Binax NOW S. pneumoniae urine antigen test was positive in 51 of 58 bacteremic pneumococcal cases (sensitivity, 88%; 95% confidence interval [CI], 77 to 95%), whereas the dual PCR was positive in 31 cases (sensitivity, 53.5%; 95% CI, 40 to 67%; P < 0.0001), and all of these had detectable urinary antigens. Both tests gave positive results in 2 of 51 control patients (referred to as other-organism septicemia), giving a specificity of 96% (95% CI, 86.5 to 99.5%). In 77 patients with nonbacteremic community-acquired pneumonia, urinary antigen was detected significantly more often (in 21 patients [27%]) than a positive result by the dual-PCR protocol (6 [8%]) (P = 0.002). The development of a dual-PCR protocol enhanced the sensitivity compared to that of the individual assays, but it is still significantly less sensitive than the Binax NOW urine antigen test, as well as being more time-consuming and expensive. Urinary antigen detection is the nonculture diagnostic method of choice for patients with possible severe pneumococcal infection.